THE ROLE OF THE TRANSPORTATION DEPARTMENT IN IMPROVING THE PUBLIC SERVICE QUALITY ON THE LAND TRANSPORTATION FIELD AT DOMPU REGENCY - Kurniasi, Ayu; Sutarna, Iwan Tanjung; Hidayat, Rahmad (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2024)
Transportation is a basic need for various communities, which helps in mobilizing passengers and goods from one place to another as well as facilitating connectivity. Therefore, this study aims to determine the role of the Transportation Department in improving public service quality in the land transportation field at Dompu Regency. The study procedures were carried out using qualitative methods by collecting data through interviews, observation, and documentation. The data obtained were analyzed using interactive methods. The results showed that the role of the Transportation Department of Dompu Regency in improving public service quality in the land transportation field was evident through various aspects. These included 1) Physical evidence (Tangibles), namely fully meeting quality in terms of procurement of facilities and the provision of good service by officers, 2) Reliability, where the service was running according to the SOP, 3) Responsiveness, namely providing appropriate and careful service, but there were still time constraints, 4) Assurance, where the need to increase the time guarantee and the cost guarantee provided was appropriate, and 5) Empathy, namely demonstration of good quality by officers. This study also revealed the presence of active, participative, and passive role. Keywords: Public Service, Land Transportation, Service Quality.